Investigating Web Search Strategies and Forum Use to Support Diet and Weight Loss - shraefel, mc; White, Ryen W.; Andre, Paul; Tan, Desney ((2009) Extended Abstracts at CHI 2009 Conference on Human Factors in Computing Systems, 2009)
Healthcare is shifting from being reactive to preventive, with a focus on maintaining general wellness through positive decisions on diet, exercise, and lifestyle. In this paper, we investigate search behavior as people navigate the Web and find support for dietary and weight loss plans. Inspecting the Web search logs of nearly 2,000 users, we show that people progressively narrow their searches to support their progress through these plans. Interestingly, people that visit online health forums seem to progress through the plans‟ phases more quickly. Based on these results, we conducted a survey to further explore the roles and importance of online forums in supporting dieting and weight loss.